Sosialisasi dan Edukasi tentang Vaksinasi Covid-19 pada Masyarakat Desa Serdang Kecamatan Tanjung Bintang Kabupaten Lampung Selatan - Ahmad Syarifudin; Helen Widyastuti; Reonika Puspita Sari; Nimas Ade Latifah (JPM: Jurnal Pengabdian Masyarakat, 2022)
Vaccination is one of the effort to stop Covid-19. But vaccination as a government program face problem cause people are afraid of being vaccinated, implications of hoax news on social media. This program to inform and educate people about vaccine and vaccination in Desa Serdang Tanjung Bintang District, South Lampung Regency, Lampung Province.